Management Costs as a Manifestation of Transaction Costs in Hierarchical Structures for the Coordination of Production and Exchange Processes - Plichta, Jarosław (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
According to the assumptions of representatives of institutional economics, enterprises as market institutions exist due to the existence of transaction costs in the processes of market exchange. The hierarchical structures of enterprises limit their occurrence and thus they are by definition more effective than the coordination of exchange by a market mechanism. The creation and maintenance of such structures also bring about costs. These are generally management costs, some of which are transaction costs. They result from imperfections of internal processes, information asymmetry, the division and establishment of property rights, opportunistic behaviour or specific resources involved in these processes. The article looks at the problems of management costs perceived from the institutional point of view, as transaction costs and an indication of the broad applicability of this approach, especially in the context of new phenomena and processes based mainly on modern technologies and the mechanisms of co-creating value. The considerations are of a conceptual character and are based on the achievements of various scientific disciplines.